Smart Robotic Exoskeleton: a 3-DOF for Wrist-forearm Rehabilitation - Noor Sabri Shalal; Wajdi Sadik Aboud (Journal of Robotics and Control (JRC), 2021)
In order to regain the activities of daily living (ADL) for patients suffering from different conditions such as stroke and spinal cord injury, they must be treated with rehabilitation process through programmed exercises. The human motor system can learn through motor learning. This study concerned with the rehabilitation of wrist and forearm joints to restore the ADL through designing and constructing a robotic exoskeleton. The exoskeleton was designed to rehabilitate the patients by providing a 3 degree of freedom (DOF) include flexion/ extension, adduction/abduction, and pronation/ supination movements. It is specified as being portable, comfortable, lightweight, and compatible with the human anatomical structure, in addition to providing a speed and range of motion (ROM) as that of a normal subject. It was designed with SolidWorks software program and constructed with a 3D printer technique using polylactic acid (PLA) plastic material. The overall exoskeleton was controlled with electromyography and angle information extracted using EMG myoware and gyroscope sensors respectively. it was applied for evaluation with 5 normal subjects and 12 subjects of stroke and spinal cord injury (SCI). The results were found that the exoskeleton has a strong effect on regaining muscle activity and increasing the ROMs of wrist and forearm joints. These results give proof of this exoskeleton to be used for performing physiotherapy exercises.